Commentary—The Impossibility of Finding Welfare Rights in the Constitution - Robert H. Bork (Washington University Law Quarterly, 1979)
The effect of Professor Michelman's style of argument, which has quite a number of devotees on the faculties of both Yale and Harvard, is to create rights by arguments from moral philosophy rather than from constitutional text, history, and structure. The end result would be to convert our government from one by representative assembly to one by judiciary. That result seems to me unfortunate for a variety of reasons.
Keywords: Welfare Rights; Equality